The effects of student- and teacher-led tootling on student disruptive behavior - Thoele, Jillian M.; Sayeski, Kristin L. (Frontiers in Education, 2024)
The foundation of effective management lies in the recognition and reinforcement of appropriate behaviors. Researchers have found that class-wide, group-contingency-based classroom management approaches can be an efficient and effective way to promote desired student behavior. For this study, we examined the effect of Tootling, a peer-mediated, group-contingency approach wherein students identify and report on their peers’ prosocial behaviors. We used an alternating treatment single-case research design to evaluate and compare the impact of student- and teacher-led Tootling on disruptive behavior and academic engagement for five elementary students. Student-led Tootling, teacher-led Tootling, and no-Tootling conditions were alternated daily following a systematically blocked, randomized schedule. After each series of the three conditions, a group-based concurrent chain preference assessment was conducted to determine students’ choice of condition. Disruptive behavior decreased for all five students during both student- and teacher-led conditions, and although data were variable, all five students increased academic engagement during student-led Tootling. Findings from the concurrent chain preference assessment revealed most students preferred the student-led Tootling condition. Social validity questionnaires indicated teachers preferred student-led Tootling and found it acceptable and feasible, and student questionnaires indicated they wanted to continue using Tootling in their classrooms. Maintenance data demonstrated all three teachers continued implementing student-led Tootling after the study’s completion. Delegating students to lead the intervention can support the integration and sustained use of Tootling in classrooms. One important next step is to evaluate the feasibility of student-led Tootling in early elementary classrooms. Replications are necessary to understand the effects of student-led Tootling in various settings and grade levels.